Evaluation of dengue fever vulnerability in south and southeast asian countries: A multidimensional approach - Yawen Wang; Conglu Li; Shi Zhao; Guozhang Lin; Xiaoting Jiang; Shi Yin; Mu He; Qianyu Wu; Zihao Guo; Yuchen Wei; Chao Ren; Ka Chun Chong (Journal of Infection and Public Health, 2025)
Background: Climate change is raising the risk of dengue fever outbreaks in South and Southeast Asia, where public health challenges persist. Warmer temperatures promote year-round mosquito breeding and pathogen transmission, particularly in crowded urban areas. This underscores the urgent need for a comprehensive assessment to develop effective prevention strategies and improve health outcomes. This study evaluated the relationship between dengue fever vulnerability and disease incidence in three countries in the region. Methods: Monthly dengue surveillance data from 2012 to 2018 were collected in Sri Lanka, Malaysia, and Thailand, alongside environmental and socioeconomic data. Principal component analysis and binomial regression model were used to calculate the vulnerability index and evaluate the relationship between dengue infection, vulnerability, and its seasonality. Results: The results indicated significant spatial variations in vulnerability across the three countries. High-vulnerability regions included western coastal Sri Lanka, western and southern Thailand, and eastern Malaysia, with notable seasonal fluctuations in high-risk areas. Areas with higher vulnerability levels were associated with increased dengue fever incidence rate ratios (IRRs), particularly in Sri Lanka (IRR= 1.97, 95 % confidence interval [CI]: 1.08–3.65) and Thailand (IRR= 14.56, 95 % CI: 5.55–39.90). Notably, the IRR increased significantly during the warm seasons, particularly in August in Sri Lanka (high vs. low, IRR= 6.11, 95 % CI: 2.83–13.47) and in June in Thailand (middle-high vs. low, IRR= 23.61, 95 % CI: 9.39–61.67). Conclusions: The spatial heterogeneity of dengue vulnerability suggests that targeted public health interventions are essential for mitigating dengue fever risks, particularly in regions vulnerable to climate change.